Silla Art and the Silk Road - Kwangshik Choe (International Journal of Korean History, 2014)
Western and Indian features found in Silla art, whether they came from the Western border regions of China or through a connection with China, it is recognized that there was both a direct and indirect a relationship between Silla, the West, and India. Many scholars have been interested in these aspects, conducting various studies as these factors played a large part in defining the origin of ancient culture and the process of harmonization between cultures. Through the Silk Road scholars are able to identify how Western cultures and civilizations were introduced to the Silla Dynasty. As the Korean peninsula has been a nexus for exchange between the East and the West, this paper aims to understand the meaning of the “Silk Road” and examines the actual state of cultural exchange at this historical site. Through artifacts excavated from Hwangnamdae-ch’ong (especially glass products), it has been determined that the Western and Western bordering countries of China culturally influenced the art of Silla. They also clearly prove that Buddhist sculptures from India and the Western bordering countries of China had a great impact on Silla art as well. Through these findings, it can be confirmed that from ancient times the influence of many cultures including China, the West, and the Western bordering countries of China had an impact on Korean culture. Particularly, Indian Buddhism which flowed into China and the Korea peninsula participated in the development of Silla culture and also played a significant role in the formation of traditional Korean culture.